Model‐independent approach for short‐term electric load forecasting with guaranteed error convergence. Issue 12 (1st August 2016) - Shen, Zhixi; Wu, Xiaoqin; Guerrero, Josep M.; Song, Yongduan
Abstract : High precision short‐term load forecasting is crucial for enhancing safe and effective operation of power systems. This study presents a new method for short‐term load forecasting using the concept of trajectory tracking. Unlike most existing forecasting methods, the proposed one is essentially model independent in that the corresponding forecasting algorithms are derived without the need for the specific load models. Furthermore, based upon Lyapunov stability theory, the prediction error of the proposed method is shown to converge with sufficient accuracy one gives rise to better forecasting performance.